Navigating the vestibular maze: text-mining analysis of publication trends over five decades - Wolfovitz, Amit; Gecel, Nir A.; Gimmon, Yoav; Shivatzki, Shaked; Sorin, Vera; Barash, Yiftach; Klang, Eyal; Tessler, Idit (Frontiers in Neurology, 2024)
The field of vestibulogy, encompassing the study of the vestibular system and associated disorders, has experienced notable growth and evolving trends over the past five decades. Here we explore the changing landscape in vestibulogy, focusing on epidemiology, diagnosis methods, treatment, and technological advancements.Methods: Publication data was obtained from the US National Center for Biotechnology Information (NCBI) PubMed database. The analysis included epidemiological, etiological, diagnostic, and treatment-focused studies on vestibular disorders, with a particular emphasis on changes in topics and trends of publications over time.Results: Our dataset of 39,138 publications revealed a rising trend in research across all age groups. Etiologically, benign paroxysmal positional vertigo (BPPV) and Meniere's disease were the most researched conditions, but the prevalence of studies on vestibular migraine and Cerebellar Ataxia Neuropathy Vestibular Areflexia Syndrome (CANVAS) showed a marked increase in recent years. Electronystagmography (ENG)/ Videonystagmography (VNG) and Vestibular Evoked Myogenic Potential (VEMP) were the most commonly discussed diagnostic tools, while physiotherapy stood out as the primary treatment modality.Our study presents a unique opportunity and point of view, explored the evolving landscape of vestibulogy publications over the past five decades. The analysis underscored the dynamic nature of vestibulogy, highlighting shifts in focus and emerging publications trends in diagnosis and treatment over time.